Collective local liberalism: orchestrated local governments and the expansion of the BRI - Li, Mingjiang (2025)
What drives the varied performance of the Belt and Road Initiative (BRI) projects? Can the central state’s role and the participating nations’ development needs fully account for the success or failure of individual BRI projects? This article challenges the dominant state-centric perspective, suggesting it falls short in elucidating the heterogeneous results of BRI projects. Through a comparative analysis of the Pan-Beibu Gulf Economic Cooperation Zone (PBGECZ) and the New International Land-Sea Trade Corridor (ILSTC), the study reveals the impact of local government collaboration on the efficacy of China’s foreign policy. By proposing collective local liberalism, we argue that cooperative dynamics, rather than competitive, are crucial for the success of the BRI. This nuanced approach underscores the necessity of a collaborative framework among subnational actors to enhance the execution and outcomes of BRI projects, offering a more comprehensive understanding of Chinese foreign policy.